[Sister Brendan's] talk on her visit to the Shakers. - Brendan, Sister (1970)
Formal remarks by Sister Brendan at Clarice Danielsson's workshop. She discusses the history and beliefs of the Shakers, having recently visited a Shaker community in Sabbathday Lake, Maine. She touches upon many topics including their furniture, art and ceremonies. A question and answer session follows.